TRANSFORMATIONAL LEADERSHIP IN THE MANAGEMENT OF MODERN PESANTREN - Widodo, Wahyudi (The Pontianak State Institute of Islamic Studies, 2025)
Modern pesantren face significant challenges in managing Islamic educational institutions to remain relevant in the era of globalization without losing their identity. Transformational leadership is one approach that can be applied to ensure that pesantren can develop adaptively and innovatively. This study aims to analyze the role of transformational leadership in the management of modern pesantren, focusing on strategies for enhancing human resource capacity, strengthening financial independence, optimizing technology, and establishing strategic partnerships. The research method used is a literature study (library research) with a qualitative descriptive approach. Data sources were obtained from indexed journals, academic books, and relevant policy documents. The data were analyzed using content analysis techniques with a thematic approach to identify key patterns in the implementation of transformational leadership in modern pesantren. The results indicate that transformational leadership plays a crucial role in driving positive changes in modern pesantren. Through systematic strategies, pesantren can enhance human resource capacity through leadership training and certification, strengthen financial independence by managing business units based on sharia economics and productive waqf, and optimize technology in pesantren management systems. Additionally, partnerships with universities and industries create opportunities for pesantren to continue innovating and improving their competitiveness at both national and international levels. This study contributes academically to the discourse on pesantren leadership and serves as a foundation for further empirical research. It is expected that the findings of this study can serve as a reference for pesantren administrators in implementing more effective and sustainable transformational leadership.